Melestarikan Warisan Leluhur: Sebuah Studi Kearifan Lokal dalam Masyarakat Adat Kampung Pulo Garut - Indah Khoirunnisa Tosin; Hari Rudiana; Eriwan Edna Pratama; M. Andriansah; Yadi Budiman; Jajang Hendar Hendrawan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to explore the forms of local wisdom preserved by the indigenous community of Kampung Pulo in Garut Regency, West Java, and examine their role in maintaining cultural continuity and communal identity. Kampung Pulo is known as one of the traditional Sundanese villages that firmly uphold ancestral values amidst the pressures of modernization. Using a qualitative approach with ethnographic methods, data were collected through participatory observation, in-depth interviews, and documentation. The findings reveal that the community's local wisdom is reflected in spatial arrangements, traditional ceremonies, social norms, and belief systems that are inherited across generations. Moreover, these traditions contribute to environmental conservation, social cohesion, and the transmission of values to younger generations. This study underscores the importance of preserving local wisdom as a cultural stronghold that holds not only historical value but also relevance for sustainable development and the reinforcement of local identity.